2021
DOI: 10.1016/j.radonc.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Whole lung irradiation as a novel treatment for COVID-19: Interim results of an ongoing phase 2 trial in India

Abstract: Background and Purpose The main cause of death in COVID-19 pneumonia is acute respiratory distress syndrome which is preceded by massive cytokine release. Low-dose radiation therapy (LDRT) has anti-inflammatory and immunomodulatory effects that can interfere with the inflammatory cascade, reducing the severity of associated cytokine release. Material & Methods 25 patients with RT-PCR proven COVID-19 disease were enrolled between November 2020 and May 2021. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…LDRT showed real curative benefits in the management of a variety of clinical conditions in which inflammation plays an important role, such as epicondylitis [15], osteoarthritis [16], necrotizing abscesses [17], and pneumonia. Several studies show that LDRT improves respiratory parameters and lung involvement and reduces serum inflammation markers [13,[18][19][20]. A comparative cohort study reported a reduction in mortality among moderate COVID-19 patients treated with LDRT compared to the control group [21].…”
Section: Discussionmentioning
confidence: 99%
“…LDRT showed real curative benefits in the management of a variety of clinical conditions in which inflammation plays an important role, such as epicondylitis [15], osteoarthritis [16], necrotizing abscesses [17], and pneumonia. Several studies show that LDRT improves respiratory parameters and lung involvement and reduces serum inflammation markers [13,[18][19][20]. A comparative cohort study reported a reduction in mortality among moderate COVID-19 patients treated with LDRT compared to the control group [21].…”
Section: Discussionmentioning
confidence: 99%
“…Eighty-eight percent of patients attained clinical recovery within 10 days after LDRT. No acute toxicity was found in this study either [ 25 ].…”
Section: Discussionmentioning
confidence: 74%
“…Our respiratory results are in agreement with previous published data. [22] , [23] , [24] Ameri et al [6] analyzed 9 patients treated with 0.5 or 1 Gy and found a SatO2 improvement in 64% of them 24 hours after RT. In our cohort there was significant SAFI improvement on day +3 and day +7 (p<0.01).…”
Section: Discussionmentioning
confidence: 99%